Gold‐Catalyzed Hydrofunctionalizations and Spiroketalizations of Alkynes as Key Steps in Total Synthesis. Issue 5 (18th May 2018) - Pflästerer, Daniel; Rudolph, Matthias; Hashmi, A. Stephen K.
Abstract: This contribution summarizes the application of homogeneous gold catalysis in hydrofunctionalization and spiroketalization reactions in total synthesis, the most frequent applications of gold catalysis in that sector. Abstract :